Cribriform scar revealing acute myeloblastic leukemia type 2 - Selma Benkirane; Sara Elloudi; Mounia Bennani; Niema Aqil; Zakia Douhi; Hanane BayBay; Fatima Zahra Mernissi (PAMJ Clinical Medicine, 2020)

(untitled)
Pyoderma gangrenosum is a sterile inflammatory neutrophilic dermatosis characterized by recurrent skin ulcers with mucopurulent or hemorrhagic exudate, which can be reactive to or associated with several pathologies, the search for associated pathologies must be systematic and oriented towards hemopathy in young subjects, as in the case of our patient presenting for a cribriform scar revealing an acute myeloid leukemia.